Adaptive Party Choice of Low-Ranking Males in Fission–Fusion Dynamics of Chimpanzees in Kalinzu Forest Reserve, Uganda - Shibata, Shohei; Furuichi, Takeshi; Hashimoto, Chie (MDPI AG, 2022)
Several studies have examined factors that regulate fission–fusion dynamics (FFD) in chimpanzee communities, such as receptive females, predation risks, and food availability. However, the effects of these factors vary between populations. In this study, we conducted focal animal observations of adult males in the M group in Kalinzu to examine the influence of male dominance rank, aggression from other males, the presence of females exhibiting maximum sexual swelling (MS), and fruit abundance on male tendencies of party attendance. We found that low-ranking males spent more time alone than other males when females with MS were absent. In contrast, when females with MS were present, males of all ranks showed a similar tendency of party attendance. We also found that the aggressive interactions increased with the number of males irrespective of the presence or absence of females with MS, and low-ranking males attracted aggression more frequently than higher-ranking males. These results suggest that low-ranking males frequently ranged alone to avoid aggression from other males unless they attended parties to seek mating opportunities. We conclude that low-ranking males have alternative tactics to balance the costs and benefits incurred or gained when attending parties.
We thank the National Forestry Authority of Uganda and the Uganda National Council for Science and Technology for their permission to conduct this research. We thank the local assistants for their help with field observations. We thank Hiroyuki Takemoto, Daisuke Shimizu, Akito Toge, and Shintaro Ishizuka for their help during the field research and their valuable discussions. We also appreciate the anonymous reviewers for their helpful comments on this paper.
Keywords: Pan troglodytes; aggression; fission-fusion dynamics; party size; dominance rank; Kalinzu Forest Reserve